Secondary impacts of the COVID-19 pandemic on access to oral health: an integrative review - Araujo, Monicky M.; dos Santos, Maria da Penha R.; Oliveira, Sydia (International Journal Of Community Medicine And Public Health, 2024)
The damage resulting from the pandemic will be lasting, at all levels of health care, with a strong influence on the use of dental services. This integrative review aims to identify the secondary impacts of covid-19 on access to oral health. Data were collected from SciELO, PubMed/Medline; BVS/Lilacs. The selection of studies initially occurred by reading the titles and abstracts, then selecting the articles that should be read in full. Snowball strategy was used from the selected studies. In total 388 studies were collected and 24 analyzed. After reading the texts in full, it was possible to observe that they are divided into themes: dental problems faced by users of health systems during the pandemic; immediate solutions to face the great demand for dental care; projections of public policy need for the future. Restrictions imposed on dental care had a negative impact on health services, mainly affecting the poorest segments of the population. Expanding access to dental treatments and water fluoridation are urgent measures that must be implemented, in addition to the application of public policies aimed at oral health. or, such as sitting time throughout the day, in addition to the importance to increase the physical activity pattern.